Dosimetric Evaluation of Three-dimensional Conformal Radiotherapy, RapidArc, and Hybrid RapidArc Radiotherapy Techniques for Left-sided Breast Cancer - Atul Mishra; Neha Yadav; Madhu Sharma; Kailash Kumar Mittal; Surendra Prasad Mishra; Teerth Raj Verma; Shilpa Tiwari (Journal of Medical Physics)
Objective: This study aimed to assess the irradiation techniques–three-dimensional conformal radiotherapy (3DCRT), RapidArc (RArc), and hybrid RapidArc (h-RArc)–for left-sided breast cancer patients, focusing on dose distribution in the planning target volume (PTV) and organs at risks (OARs). Materials and Methods: This study enrolled 20 patients diagnosed with early-stage left-sided breast cancer. All patients received a prescribed dose of 40.05 Gy in 15 fractions (2.67 Gy per fraction), optimized to achieve 95% dose coverage to 95% of the PTV. The dosimetric variations across the three treatment plans for the 20 patients were examined using a one-way ANOVA test. P <0.05 was regarded as statistically significant. Results: In the 3DRCT plan, D95% of the PTV was 37.21 ± 0.51 Gy. This value was significantly increased to 39.43 ± 0.27 Gy in the RArc plan (P = 0.001) and to 38.47 ± 0.19 Gy in the h-RArc plan (P = 0.630). The RArc plans demonstrated a superior homogeneity index of 0.12 ± 0.02 compared to both 3DCRT (0.18 ± 0.02) and h-RArc (0.13 ± 0.02). When comparing the increase in monitor units (MUs), h-RArc showed a 62.82% increase over 3D-CRT, whereas demonstrating a 38.05% decrease compared to RArc (P = 0.000). Conclusions: h-RArc treatment plans for breast cancer may be recommended due to their superior and consistent PTV dose coverage and sparing of OARs, in comparison to both 3DRCT and RArc plans. These h-RArc plans are characterized by reduced MU and beam on time, as well as a less low volume dose when compared to RArc plans.